Communication Behaviour of Women Vegetable Growers of Nainital District of Uttarakhand - Verma, Deepika (Indian Journal of Extension Education, 2016)
The research study was undertaken to find out information processing behaviour and approaches used by the women  vegetable growers in the six villages of Community Development Blocks, Haldwani, Ramnagar and Dhari in Nainital  district of Uttarakhand. Data were collected through pre-tested semi- structured interview schedule and Focous Group  Discussions from 150 women vegetable growers. The findings of the study revealed that the personal cosmopolite  sources, which are part of farming community, live with the farmers, aware of farmers' problems, provide new  technologies, and having close supervision, can play significant role for bringing agricultural development in the region.
Keywords: Communication sources; communication behaviour; communication approach; farm women; vegetable cultivation